Alocação adaptativa de banda e controle de fluxos de tráfego de redes utilizando sistemas Fuzzy e modelagem multifractal - Cardoso, Alisson Assis (2014)
Inthispaperweproposeafuzzymodel,calledFuzzyLMScomAutocorrela¸c˜aoMultifractal, whose weights are updated according to information from multifractal traﬃc modeling. These weights are calculated by incorporating an analytical expression for the autocorrelation function of a multifractal model in the training algorithm of the fuzzy model that is based on the Wiener-Hopf ﬁlter. We evaluate the prediction performance of the proposed network traﬃc prediction algorithm with respect to other predictors. Further, we propose a bandwidth allocation scheme for network traﬃc based on the fuzzy prediction algorithm. Comparisons with other bandwidth allocation schemes in terms of byte loss rate, link utilization, buﬀer occupancy and average queue size veriﬁes the eﬃciency of the proposed scheme. Also, We propose an other adaptive fuzzy algorithm, called Fuzzy-LMS-OBF com alfa adaptivo , for traﬃc ﬂow control described by theβMWM model. The proposed algorithm uses Orthonormal Basis Functions (OBF) and its training based on the LMS algorithm. We also present an expression for the optimal traﬃc source rate derived from Fuzzy LMS. Then, we evaluate the performance of the Fuzzy-LMS-OBF com alfa adaptivo algorithm with respect to other methods. Through simulations, we show that the proposed control scheme is beneﬁted from the superior performance of the proposed fuzzy algorithm. Comparisons with other methods in terms of mean and variance of the queue size in the buﬀer, Utilization rate of the link, Loss rate and Throughput are presented.